ANALISIS RESIKO ERGONOMI PADA PEKERJA DI PT ABC - Sisnandar, Mochamad Triadi; Sirait, Ganda (LPPM Universitas Putera Batam, 2021)
This research is conducted on aircraft structure workers at PT ABC, Batam. To determine the level of ergonomic risk and an overview of MSDs complaints experienced by workers. The design of this research is Analytical descriptive Cross Sectional. This research was carried out by observation and giving questionnaires to aircraft structure workers are working in lower fuselage. The results obtained in this study have a high risk (10) in the activity of dismantling the tail skid in the lower fuselage, the most common subjective complaint of MSDs that is felt in the waist and upper neck (85%). The Pearson correlation test shows that there is no correlation between age, sex, work experience, and smoking habits in MSDs complaints. therefore, need improvement steps from PT ABC management.